Repositioning Outsourcing as an Employment Alternative: An Analysis of the Ijarah Contract at PT Berkat Rezki Nusantara - Siswandi Siswandi; Muzalifah Muzalifah (Program Studi Ekonomi Syariah Institut Agama Islam Darullughah Wadda'wah, 2026)
This study aims to analyze outsourcing practices as an alternative to traditional employment from an Islamic economics perspective through the Ijarah al-A‘mal contract approach and to assess the resulting maslahat. This study employs a qualitative approach with a case study design at PT Berkat Rezki Nusantara. Data were collected through in-depth interviews, observations, and documentation, then analyzed using the Miles and Huberman interactive analysis model. The results indicate that the implemented outsourcing practices have fulfilled the basic elements of the Ijarah contract, including clarity regarding the parties involved, the scope of work, wages (ujrah), and mutual agreement. The resulting employment relationship also demonstrates a tripartite relationship between the outsourcing firm, the client company, and the workers, which, from a fiqh muamalah perspective, can be understood as a form of parallel ijarah. Furthermore, outsourcing functions as an adaptive labor mechanism in facilitating access to employment and ensuring income stability, particularly for workers affected by changes in labor policies. From an Islamic economics perspective, this practice generates tangible maslahat, particularly in maintaining workers’ economic stability, although limitations remain in the form of disparities in benefits and job security compared to permanent employees. This study concludes that outsourcing cannot be evaluated dichotomously as a system that is purely detrimental or beneficial but must be understood contextually. As long as it is implemented based on the principles of justice, transparency, and clarity of contracts, outsourcing can be repositioned as a relevant labor mechanism from an Islamic economics perspective.